Long-term follow-up of pediatric MS patients starting treatment with injectable first-line agents: A multicentre, Italian, retrospective, observational study. (March 2019) - Baroncini, Damiano; Zaffaroni, Mauro; Moiola, Lucia; Lorefice, Lorena; Fenu, Giuseppe; Iaffaldano, Pietro; Simone, Marta; Fanelli, Fulvia; Patti, Francesco; D'Amico, Emanuele; Capobianco, Marco; Bertolotto, Antonio; et al.
Background: Few data are available on very long-term follow-up of pediatric multiple sclerosis (MS) patients treated with disease modifying treatments (DMTs). Objectives: To present a long-term follow-up of a cohort of Pediatric-MS patients starting injectable first-line agents. Methods: Data regarding treatments, annualized relapse rate (ARR), Expanded Disability Status Scale (EDSS) score, and serious adverse event were collected. Baseline characteristics were tested in multivariate analysis to identify predictors of disease evolution. Results: In total, 97 patients were followed for 12.5 ± 3.3 years. They started therapy at 13.9 ± 2.1 years, 88 with interferons and 9 with copaxone. During the whole follow-up, 82 patients changed therapy, switching to immunosuppressors/second-line treatment in 58% of cases. Compared to pre-treatment phase, the ARR was significantly reduced during the first treatment (from 3.2 ± 2.6 to 0.7 ± 1.5, p  < 0.001), and it remained low during the whole follow-up (0.3 ± 0.2, p  < 0.001). At last observation, 40% had disability worsening, but EDSS score remained <4 in 89%. One patient died at age of 23 years due to MS. One case of natalizumab-related progressive multifocal encephalopathy (PML) was recorded. Starting therapy before 12 years of age resulted in a better course of disease in multivariate analysis. Conclusion: Pediatric-MS patients benefited from interferons/copaxone, but the majority had to switch to more powerful drugs. Starting therapy before 12 years of age could lead to a more favorable outcome.